Natural history and genotype‐phenotype correlations in 72 individuals with SATB2‐associated syndrome. Issue 4 (13th February 2018) - Zarate, Yuri A.; Smith‐Hicks, Constance L.; Greene, Carol; Abbott, Mary‐Alice; Siu, Victoria M.; Calhoun, Amy R. U. L.; Pandya, Arti; Li, Chumei; Sellars, Elizabeth A.; Kaylor, Julie; Bosanko, Katherine; Kalsner, Louisa; et al.
Abstract : SATB2‐associated syndrome (SAS) is an autosomal dominant disorder characterized by significant neurodevelopmental disabilities with limited to absent speech, behavioral issues, and craniofacial anomalies. Previous studies have largely been restricted to case reports and small series without in‐depth phenotypic characterization or genotype‐phenotype correlations. Seventy two study participants were identified as part of the SAS clinical registry. Individuals with a molecularly confirmed diagnosis of SAS were referred after clinical diagnostic testing. In this series we present the most comprehensive phenotypic and genotypic characterization of SAS to date, including prevalence of each clinical feature, neurodevelopmental milestones, and when available, patient management. We confirm that the most distinctive features are neurodevelopmental delay with invariably severely limited speech, abnormalities of the palate (cleft or high‐arched), dental anomalies (crowding, macrodontia, abnormal shape), and behavioral issues with or without bone or brain anomalies. This comprehensive clinical characterization will help clinicians with the diagnosis, counseling and management of SAS and help provide families with anticipatory guidance.